CLARIFYING THE POWER OF THE SOUTH AFRICAN HUMAN RIGHTS COMMISSION TO TAKE STEPS TO REDRESS THE VIOLATION OF HUMAN RIGHTS: A DISCUSSION OF South African Human Rights Commission v Agro Data CC [2022] ZAMPMBHC 58 - Slade, Bradley (Obiter, 2023)
This case note proceeds as follows. First, it sets out the powers of the Commission in terms of the Constitution and the South African Human Rights Act (40 of 2013) (the Act), before turning to a discussion of Agro Data and considering the implications that this decision may hold for the power of the Commission, specifically as far as it relates to taking “steps to secure redress where human rights have been violated”.